Electrochemical Sensor for Determination of Parathion Based on Electropolymerization Poly(Safranine) Film Electrode - Xingyuan Liu (International Journal of Electrochemistry)
Parathion has been determined with voltammetric technique based on a novel sensor fabricated by electropolymerization of safranine on a glassy carbon electrode (GCE). The electrochemical behavior of poly(safranine) film electrode and its electrocatalytic activity toward parathion were studied in detail by cyclic voltammetry (CV) and linear sweep voltammetry (LSV). All experimental parameters were optimized, and LSV was proposed for its determination. In optimal working conditions, the reduction current of parathion at this poly(safranine)-modified electrode exhibited a good linear relationship with parathion concentration in the range of 3.43×10−8 to 3.43×10−5 mol L−1. The detection limit was 1.0×10−8 mol L−1. The high sensitivity and selectivity of the sensor were demonstrated by its practical application for the determination of trace amounts of parathion in fruit samples.